Jane Austen's View on the Industrial Revolution in Pride and Prejudice - Aralia Heaverly; Elisabeth Ngestirosa EWK (Linguistics and Literature Students' Journal, 2020)
This study dismantles Jane Austen’s view in Pride and Prejudice novel triggered by the social systems in British society. The society influenced by the phenomena of the industrial revolution in England in the late eighteenth century revealed the social system. This study aims to find out how Jane Austen views the revolution of the industry in British society. By having the focus on the sociology of literature, this study applies Lucien Goldman’s genetic structuralism. By the dialectical method, the study found that in Austen’s view the landed gentry system and inheritance system was adopted to measure the social class among the societies. Jane Austen thought the inheritance system as the fallacious practice in the society as the economic condition motivated British parents to apply matchmaking for their children to get a better life. Jane Austen views that the industrial revolution plays an important role in forming social occupation at that time. The working-class condition leads them to work in the town, while the upper-class society tends to open some businesses by doing trade at the town. The rest group of middle class tends to work and dedicate themselves to the rich people. Finally, Jane Austen puts her view toward the society in Pride and Prejudice.Keywords: author, class, genetic structuralism, the industrial revolution, view